(untitled) (REMUNOM, 2025)
This scientific article analyzes the role of Alternative Dispute Resolution Methods in addressing the Brazilian Judiciary’s delays in resolving lawsuits filed in court, particularly in the lower courts. The approach provides a contemporary reflection on the fundamental role played by conciliation and mediation. The figures in the National Council of Justice’s yearbooks clearly illustrate the situation in the various courts that make up the Brazilian Judiciary. The study conducted for this article revealed that, without the use of Alternative Dispute Resolution Methods, such as conciliation, mediation, and arbitration, the current situation will not improve. However, the use of these methods has demonstrated that it is possible to address the delays in resolving judicial disputes. With this perspective in mind, there was mobilization of the Legislative and Judicial Powers, with the creation of instruments that favored the use of these methods in the various areas of Brazilian justice, notably the inclusion in Law 13.105/2015 (Code of Civil Procedure) and Resolution 125/2010, of the National Council of Justice, which instituted the National Judicial Policy for the Appropriate Treatment of Conflicts of Interest.